A study on substitution characteristics and competitive performance of Chinese super league teams under the five-substitution rule - Tong Chen; Liang Chen (PLoS ONE, 2025)
Under the revised substitution regulations in soccer, this study aims to analyze the performance characteristics of substitution events in Chinese Football Association Super League (CSL) matches and explore the relationship between soccer substitution networks and team performance over the season. Using non-goalkeeper substitution events (n=2125) from the 2023 CSL season as the research sample, the study conducted substitution network modeling and clustering to investigate the relationship between network characteristics and team performance, as well as the performance traits of different types of substitution events. Results showed that professional soccer teams with higher substitution network density demonstrated better performance in goal difference and goals conceded. Out-degree centralization positively influenced goal difference, goals scored, and team ranking, while higher In-degree centralization correlated with fewer goals conceded. Additionally, players with more balanced on-field participation were substituted most frequently. Offensive players with strong attacking abilities were substituted in earlier, while wide players were the most frequently substituted out. Players with a high frequency of high-risk passes were substituted out later. Therefore, a substitution strategy centered around some soccer players contributes to better seasonal performance. Substitutions out of players are more focused on physical condition, with high-performing teams tending to substitute out similar types of players at different times. Substitutions in, on the other hand, emphasize the compatibility of player abilities. Under the “five substitutions” rule, greater attention is given to the running distance and maximum sprint speed of soccer substitute players.